Observation of four-electron Auger processes. (August 2015) - Müller, A; Borovik, A; Buhr, T; Hellhund, J; Holste, K; Kilcoyne, A L D; Klumpp, S; Martins, M; Ricz, S; Viefhaus, J; Schippers, S
Synopsis: Absolute cross sections for triple photoionization of C + ions have been measured. Direct triple-Auger decay of K-shell excited states, i.e., an interaction process involving four electrons that results in the simultaneous emission of three electrons, could be unambiguously observed and quantified.